Implementation of P5 Activities in the Independent Curriculum at Elementary Schools - Rahmanita, Rahmanita; Putri, Maharani; Yanti, Novia (International Journal of Multidisciplinary Research of Higher Education, 2025)
This study was motivated by learning activities using the independent curriculum related to P5 activities at a state elementary school in Indonesia. These activities are in line with the independent curriculum, in which all students and teachers are involved in carrying out P5 activities. This study aims to determine the time allocation for P5 activities, the themes chosen by students, and the benefits of P5 activities for students. The method used is qualitative with an ethnographic approach (study of culture and social behavior) in the school environment. The research data sources use primary and secondary data, namely the principal, teachers, and students. Data collection techniques were carried out through observation, interviews, and documentation. The data validity technique used is data source triangulation. The results of this study show that P5 activities are carried out at the end of the semester after the completion of semester exams by determining activity themes such as traditional skills, culture, cooking, recreation, and others. Meanwhile, the benefits gained from these activities include many experiences for students in displaying their creativity and establishing relationships with one another.